Tourism and the implications of transformation for Sustainable Development Atheoretical study - Dr. Salem Hamid Salem (Research Parks Publishers, 2023)
The research aims to draw attention to and gain insight into the contents, opinions and perceptions of the topic of Tourism and the implications of transformation for sustainable development, not limited in its orientations to responding to the requirements of Tourism and the labor market, because of its importance and value in the application of the Sustainable Development Goals, as well as this topic acquires other importance that clearly reflects the ability in transformation for sustainable tourism development as a result of the theses and ideas submitted by specialists in various scientific fields of studies and research in the subject of research to benefit from them .The researcher also dealt with an inductive theoretical analysis of the content of this effort aimed at establishing an understanding of the meaning of tourism in the framework of the Sustainable Development Goals and in the direction of supporting ideas supporting The research problem is caused by the deterioration of tourist attractions as a result of the waste of resources and excessive and absurd use of tourist resources. In line with the research methodology, the researcher tries to use the logical and inductive method as a way of conclusion based on putting forward logical concepts that do not deviate from the controls of scientific research .In order to develop theoretical ideas supported by some cases. The study was limited to reviewing and analyzing the most prominent concepts that dealt with the topic of Tourism and the implications of transformation for Sustainable Development.